Circu-lando na escola: uma proposta pedagógica do ensino do circo - Caliman, Danielly Gomes (2023)
The circus is one of the manifestations of body culture that can be worked pedagogically in school physical education classes. Considering this content as relevant in the education of children, this research aimed to present the circus culture to students of the 3rd and 4th years of Elementary School I. This proposal was carried out through playful didactic activities, adopting the critical-surpassing methodology in its diagnostic, judictive and teleological axes, to teach circus activities not only under the bias of knowledge production, but rebuild it within the possibilities of the school. This is an intervention research, of the participant type, in which observation was used to obtain the data produced in the intervention process. The circus activities were carried out during physical education classes held from March 8 to June 14, 2022. The classes were taught by the teacher/researcher and occurred in the available spaces of the school, such as classroom, patio, reading square. For the registration of classes, a field notebook, photos and filming was used with the authorization and consent of the students and their guardians. After the classes, a critical and reflective analysis was made. As a result, the students had contact with this knowledge, which allowed the revival of imagination and the learning of gestures and experiences of body practices in which the circus is inserted. The students also demonstrated to appropriate what they were taught and resignify their learning from the concrete relationships experienced at school, in which cooperation, complicity, companionship, respect, trust, joy were fundamental points for their development. They were also able to seize, rework and create the school circus. The teacher, in turn, can overcome her empirical experience and rethink her pedagogical practice.